Hot Deformation Behavior and Hot Processing Map of 50CrVA Spring Steel - Yang Zhao; Jian Zheng; Zhi Liu; Liqing Chen (Metals, 2024)
It is important to explore the hot deformation behavior and establish the hot processing map of steel to design and optimize the hot rolling process. In this paper, 50CrVA spring steel was used as the experimental material. Single-pass compression tests were performed at 850–1150 °C and 0.01–5 s−1 on an MMS-300 thermo-mechanical simulation testing machine to investigate the hot deformation behavior and establish the hot processing map. The results show that as the strain rate increases and the deformation temperature decreases, the flow stress of 50CrVA spring steel increases. The constitutive equation of 50CrVA spring steel is <semantics><mover accent="true">ε˙</mover>=1.01×1014[sinh(0.0094σp)]4.53exp(−<mstyle scriptlevel="0" displaystyle="true">364,470RT</mstyle>)</semantics>. The dynamic recrystallization critical strain model is <semantics>εc=4.19×10−3Z7.31×10−2</semantics>. A hot processing map of 50CrVA spring steel was constructed to determine the plastic instability region and optimal hot working region.